Ultrasound-guided Transvaginal Aspiration in the Management of Actinomyces Pelvic Abscess - Eyal Y. Anteby; Galiya Rahav; Josef Hanoch; Shlomo Shimonovitz; Simcha Yagel; Neri Laufer (Hindawi Limited, 1996)
Background: Increasing reports of intrauterine device (IUD)-related abdominopelvic actinomycosis have been described recently. Surgical therapy has been the usual treatment when tubo-ovarian abscess is identified.